PENGARUH SOCIAL MEDIA MARKETING DAN KREDIBILITAS INFLUENCER TERHADAP PURCHASE INTENTION MELALUI BRAND IMAGE TERHADAP PT XYZ - Hidayati, Uci Nurul; Samuel Tarigan (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
The rapid growth of social media has significantly transformed marketing strategies in the service industry, including the airline sector. PT XYZ, as Indonesia’s national full-service airline, utilizes social media marketing and influencer collaborations to strengthen brand image and stimulate consumers’ purchase intention. However, empirical evidence regarding the effectiveness of these strategies in influencing purchase intention through brand image remains limited. This study aims to examine the effect of social media marketing and influencer credibility on purchase intention through brand image at PT XYZ. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 150 respondents who actively use social media and are familiar with or have used PT XYZ services. Data analysis was conducted using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. Instrument testing included validity and reliability tests, followed by hypothesis testing to analyze the relationships among variables. The results indicate that social media marketing and influencer credibility have a positive and significant effect on brand image. Brand image also has a significant influence on purchase intention and is identified as the strongest determinant of consumers’ buying intention. Furthermore, brand image acts as a partial mediating variable between social media marketing, influencer credibility, and purchase intention. This study concludes that strengthening brand image is essential for enhancing the effectiveness of digital marketing strategies at PT XYZ. Future research is recommended to incorporate additional variables such as brand trust or customer satisfaction and to apply longitudinal data to obtain more comprehensive findings.